Phillip Bassett-Cowen interviewed by Lyn McLeavy in the Bringing them home oral history project - Bassett-Cowen, Phillip, 1951-; McLeavy, Lyn, 1948- (2001)
Bassett-Cowen was removed as a baby and placed in a Salvation Army institution in Hobart. His father's Aboriginal family tried unsuccessfully to claim him, but he was adopted by a white family in 1953. Bassett-Cowen left home at the age of 17 and worked in a variety of jobs in Tasmania and on the mainland. He is currently studying for his Bachelor of Arts degree. He located his Aboriginal family around 1989. He talks about the long-term effects of separation and childhood abuse on his life.
Aboriginal and Torres Strait Islander people are advised that this recording may contain names and voices of deceased persons.
Recorded on July 5, 2001 at Launceston, Tas.
Digital master available
Timed summary (3 p.) and uncorrected transcript (typescript, 46 leaves)
Keywords: Bassett-Cowen, Phillip, -- 1951- -- Interviews; Child welfare - Child / parent separation - Stolen generations; Child welfare - Adoption and fostering; Aboriginal Australians -- Ethnic identity -- Tasmania; Children, Aboriginal Australian -- Care -- Tasmania; Family reunification -- Tasmania